Sustainable Capture of Aromatic Volatile Organic Compounds by a Pyrene-Based Metal-Organic Framework under Humid Conditions - Sudan, Sylvain; Gladysiak, Andrzej; Valizadeh, Bardiya; Lee, Jung-Hoon; Stylianou, Kyriakos C. (AMER CHEMICAL SOC, 2020)
The threat posed by the presence of artificial volatile organic compounds (VOCs) in the environment is a widely acknowledged fact, both for environmental issues and human health concerns. Ever-increasing production requires the continuous development of technologies toward the removal of these substances. In recent years, metal-organic frameworks (MOFs) have shown a great promise toward the capture of VOCs, but their stability in humid conditions still remains a major challenge, thus hindering their widespread development. To tackle this obstacle, we designed a 3-dimensional and porous MOF, named SION-82, for the capture of small aromatic VOCs, relying solely on p-p interactions. SION-82 captures benzene efficiently (107 mg/g) in dry conditions, and no uptake decrease was observed in the presence of high relative humidity for at least six cycles. Unlike HKUST-1 and MOF-74(Co), SION-82 possesses two vital characteristics toward sustainable benzene capture under humid conditions: moisture stability and reusability. In addition, SION-82 captures benzene under humid conditions more efficiently compared to the hydrolytically stable UiO-66, highlighting the impact of having an active site for benzene capture that is not affected by water. SION-82 can additionally capture other aromatic VOCs, showing pyridine and thiophene uptake capacities of 140 and 160 mg/g, respectively.
Keywords: CO2 CAPTURE; ADSORPTION PROPERTIES; WATER STABILITY; FLUE-GAS; CHEMISTRY; UIO-66-NH2; THIOPHENE; ADSORBENT; BENZENE; MOF